2004
DOI: 10.1128/aem.70.4.2474-2485.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Associated with Morphology in Aspergillus niger by Using Suppression Subtractive Hybridization

Abstract: The morphology of citric acid production strains of Aspergillus niger is sensitive to a variety of factors, including the concentration of manganese (Mn 2؉ ). Upon increasing the Mn 2؉ concentration in A. niger (ATCC 11414) cultures to 14 ppb or higher, the morphology switches from pelleted to filamentous, accompanied by a rapid decline in citric acid production. The molecular mechanisms through which Mn 2؉ exerts effects on morphology and citric acid production in A. niger cultures have not been well defined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 61 publications
1
32
0
1
Order By: Relevance
“…Transcriptomics work on A. niger SSF is limited and the situation for Aspergillus biofilms is minimal but interesting work was published on SCF for several features [92][93][94][95][96]. Some results obtained with A. fumigatus biofilms have been already discussed elsewhere [1].…”
Section: Transcriptomicsmentioning
confidence: 95%
“…Transcriptomics work on A. niger SSF is limited and the situation for Aspergillus biofilms is minimal but interesting work was published on SCF for several features [92][93][94][95][96]. Some results obtained with A. fumigatus biofilms have been already discussed elsewhere [1].…”
Section: Transcriptomicsmentioning
confidence: 95%
“…The appearance of more than one band for a specific gene is usual in transcriptional studies by RT-PCR (Donzelli and Harman 2001;Dai et al 2004;Damveld et al 2005) and it can be explained in part due to the presence of similar enzyme-encoding Figure 1. Differential expression analysis of genes coding for some lignocellulolytic enzymes (see Table 1) in Aspergillus niger grown in biofilm fermentation (BF) and submerged fermentation (BF).…”
Section: Resultsmentioning
confidence: 99%
“…160 Another study found that overexpression of citrate synthase did not increase the rate of CA production. 165 A double mutant A. niger strain, which lacks both glucose oxidase (goxC) and oxaloacetate acetylhydrolase (prtF), was created to prevent oxalate and gluconic acid formation. 162,163 Nevertheless, there have been some successful attempts to enhance CA production through indirect means.…”
Section: Citric Acidmentioning
confidence: 99%